UJI DOSIS DAN FREKUENSI APLIKASI PUPUK UREA TERHADAP PERTUMBUHAN BIBIT JATI PUTIH (Gmelina arborea Roxb.) - Riyanto, Agung Budi; Patola, Efrain -; -, Siswadi - (Innofarm:Jurnal Inovasi Pertanian, 2013)
Research on the "Test of Dosage and Frequency of Urea Fertilizer Applications To Growth of White Teak Seedlings (Gmelina arborea Roxb.)â€ Â has been started on May 12 to July 26, 2013 at green house of agriculture faculty of Slamet Riyadi University which is located in Village Kadipiro, Subdistrict Banjarsari, Town Surakarta, Province Central Java. This study aims to determine the best dosage and frequency of urea fertilzer application Â as well as to determine interaction between dosage and frequency of urea fertilzer application on the growth of White Teak seedlings. The research designÂ  was factorial Completely Randomized Design (CRD, consisted of 2 factors and 3 replications. Data Â were Â analyzed Â by Â Analysis Â of Â Variance Â (Anova), Â continued Â by Â Honestly Significant Diferent Test (HSDT) on 5 % significant level. Results of this study showed that the dosage of urea fertilizer significantly affected all growth parameters namely height of seedling, diameter of stem, number of leaf, area of leaf fresh weight of root, dry weight of root, fresh weight of seedling and dry weight of seedling. While the frequency of urea fertilzer application significantly affected only on area of leaf, fresh weight of root, and dry weight of root. Interaction between dosage and frequency of urea fertilizer application Â did not significantly affect all growth parameters. Treatment which gives the best effect on all parameters fertilizer growth is 0.50 g / seed / application and frequency of 2 weeks. Key words : Dosage,Frequency , Urea Fertilizer,White Teak, Seedlings